2021
DOI: 10.9734/jocamr/2020/v12i330209
|View full text |Cite
|
Sign up to set email alerts
|

Perception and Acceptance of Herbal Medicines among Residents of Port Harcourt, Nigeria

Abstract: Background: The use of herbal medicines and medicinal plants available in a locality in the treatment and control of human diseases, promotion of health and management of health conditions will continue to play a significant role in the healthcare system of the people, especially in developing countries. This cross-sectional study was carried out to assess the perception and knowledge of usage of herbal medicines among the residents of Port Harcourt, Nigeria. Methodology: Multi-stage sampling technique was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 11 publications
7
2
0
Order By: Relevance
“…There is therefore the need for health authorities to verify and ensure that detailed pharmacotherapeutic data on all traditional medicines of interest is made available to health care providers before their integration into the health care system. This above finding agrees with other works in Cameroon [ 15 ] and Nigeria [ 27 ], where most people perceive traditional medicines as efficacious, cost-effective and a viable alternative to orthodox medicine. This observation agrees with the general belief among most people that herbal medicines are effective, affordable, and safe [ 41 ].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…There is therefore the need for health authorities to verify and ensure that detailed pharmacotherapeutic data on all traditional medicines of interest is made available to health care providers before their integration into the health care system. This above finding agrees with other works in Cameroon [ 15 ] and Nigeria [ 27 ], where most people perceive traditional medicines as efficacious, cost-effective and a viable alternative to orthodox medicine. This observation agrees with the general belief among most people that herbal medicines are effective, affordable, and safe [ 41 ].…”
Section: Discussionsupporting
confidence: 92%
“…A study in Bauchi, Nigeria revealed that over one-third of participants combined herbs with orthodox medications and over four-fifth of them did not inform their doctors that they used herbs [ 29 ]. In line with reports from previous surveys that females are more prone to use Complementary” “Alternative” medicine (CAM) than males [ 27 , 34 – 37 ], the proportion of herbal tea use among females in this study was slightly higher than in males, for both community and hospital respondents in the current study. Women consider traditional medicine to be safe for their health, especially in consideration of their reproductive health, including pre-natal and post-natal health, pregnancy outcomes and breastfeeding [ 38 , 39 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations